Human capital of school-age population in West Sumatera: measurement and determinant - Firlan Firlan; Werry Darta Taifur; Indrawari Indrawari (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
Information on human capital, especially for school- age population is still limited. Most of Indicators of human capital only consider the dimensions of education, while human capital is formed by various dimensions not only education. Recent human capital measurement is displayed in macro level so that difficult to analys in micro level. Based on recent condition of human capital information, this study aims to measure the human capital of the school-age population of 7-18 years old using the fuzzy set approach by considering several dimensions of human capital investment and analysis the determinant. The data source is from West Sumatera Socio-Economic Survey that held by National Bureau of Statistic in March 2017. Measurement human capital of 9,950 samples of school age population shows that urban areas have higher human capital than the rural areas. Internal factors, household and spouse characteristics such as income, parent education and occupation have impact in their children human capital. External factors such as subsidies and rural-urban development inequality also have impact and tend to be larger than internal factor. The strategy of increasing human capital under conditions of limited resources can be achieved by increasing the index of indicators which have greatest weight and also reducing development inequality between urban and rural areas. The other policy is to realize growth economic that have positive impact to entire society. In terms of methodology, this approach can be adapted to regional conditions, the development of theory and related research. Adjustments can be made at the stage of selecting investment indicators, data types and weight of indicator